Substitute Public Notary Accountability Process The Negligent In Agreement (Case Study In Semarang) - Angga Wisnu Firmansyah; Maryanto Maryanto (Jurnal Akta, 2018)
Notary is within the meaning of the Act No. 30 of 2004 concerning Notary in Article 1 is mentioned sense Public notary officials who are authorized to make an authentic agreement and other authorities referred to in this Act. But not forever Notaries can continue to work, in this case, a notary can appoint a replacement to run the temporary Notary and his task. Substitute Notary has the same authority to the notary replaces. With their equality between the legal position with the Substitute Public Notary, then there are no doubts anymore that the agreement made by Notary Substitutes have the same legal force by agreement of Notary. This study is a socio-juridical, then studied at first is by using secondary data library materials and then proceed with research on primary data obtained from the field by taking into account the applicable legal norms connected with the facts found from the study.Keywords: Authority; Notary; the Notary Substitute Responsibility.